MODEL ACADEMIC BURNOUT PADA KARYAWAN YANG MELAKUKAN STUDI LANJUT - Putri, Mutiara Ramadhona; Anindita, Rina (JURNAL LENTERA BISNIS, 2026)
Education is one of the key factors that can enhance an individual's career opportunities. However, once employed, individuals often hesitate to pursue further education due to concerns about increased burdens, such as stress and fatigue. This study aims to confirm and predict how employees who continue their studies remain productive, by examining the interrelationships among the variables of Stress, Quality of Work Life, Psychological Well-Being, Academic Burnout, and Perceived Productivity. A total of 145 full-time employees who are also pursuing further education participated in this study. Data were collected through an online questionnaire distributed in the regions of Jakarta, Bekasi, and Tangerang. The study employed a quantitative research method and was analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS).The findings reveal that stress negatively affects psychological well-being and positively influences academic burnout. Quality of work life significantly impacts psychological well-being. Furthermore, psychological well-being was found to enhance perceived productivity and also influence academic burnout. However, academic burnout was not found to have a significant effect on perceived productivity. The implication for organizations is that they should support employees who wish to pursue further education, as it does not diminish their productivity.